Co-evolution of port business ecosystem based on evolutionary game theory - Wenjuan Li; Thierry Vanelslander; Gang Li; Xu Xu (Journal of Shipping and Trade (JST), 2020)
As distributing centres of trade and transportation network, ports play an important role in the development of the national economy. With the changing of the global business environment, the port enterprise operation environment is continuously changing, and growing problems are becoming increasingly complex. Since challenges, uncertainties, risks, and crisis exist side by side, it is indispensable and beneficial to do a systematic analysis of the development of port enterprises from the perspective of biological co-evolution. This paper uses the evolutionary game model to discuss the dynamic change process and evolutionary stable strategy of the collaborative development of the core enterprise and cooperative enterprise in the port business ecosystem. Then, the influencing factors of enterprise decision-making or action selection are analysed, and the numerical model verifies the accuracy of the model. Finally, suggestions on the development of the port business ecosystem are put forward.
Keywords: 650; Port business ecosystem; Core enterprise; Cooperative enterprise; Evolutionary game